Semangat dan Militansi Keislaman Kaum Muda di Ruang Publik - Alam, Lukis; Aminah, Aminah (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2017)
This study examines the dynamics of university students in fighting for their aspiration to uphold Islam in the public sphere. For their presence, mosque and campuses become their ideological base camp and Islamic thought. Islam and young people have become a special identity that negotiates with modernity. This study aims to provide a critical view on the prolongation of youth in understanding the reality of Islam in the public sphere, affected by the social and political situation in Indonesia during the New Order and post-reform era. In addition, it would provide a perspective on the identity of young people who take Islamic symbols in promoting for their ideation into the public sphere Yogyakarta City is selected as fieldwork location because the progressiveness of youth and Islam is increasing, and as the city of education centre Yogyakarta plays a role in transforming the Islamic culture of a new model for young people.